Harnessing the therapeutic potential of fisetin and its nanoparticles: Journey so far and road ahead. (1st April 2022) - Vishwas, Sukriti; Singh, Sachin Kumar; Gulati, Monica; Awasthi, Ankit; Khursheed, Rubiya; Corrie, Leander; Kumar, Rajan; Collet, Trudi; Loebenberg, Raimar; Porwal, Omji; Gupta, Saurabh; Jha, Niraj Kumar; et al.
Abstract: Fisetin (FS) is a bioactive flavonoid obtained mostly from apple and strawberry and classified under the category of food supplements due to numerous pharmacological effects against various diseases through multiple mechanistic pathways. It acts as excellent neuroprotective, cardioprotective, anti-invasive, anti-tumorigenic, anti-angiogenic, anticancer, antidiabetics, antioxidant, anti-inflammatory agent. Despite having excellent safety and efficacy profile, FS is very less explored to clinical research either as food supplement or, as therapeutic agent due to its poor aqueous solubility, low bioavailability and reduced blood brain barrier permeability. Multiple mechanistic pathways through which FS elicits its pharmacological actions and the challenges associated with FS that compromises therapeutic efficacy are described in this article. The nanoformulations developed to enhance the bioavailability and therapeutic efficacy of FS are also covered with detailed description of research works carried by various researchers. These include nanoemulsions, liposomes, ethosomes, glycerosomes, polymeric micelles, self-nanoemulsifying drug delivery system and polymeric nanoparticles. Various patents pertaining to extraction/isolation, formula composition and therapeutic uses of FS as well as some clinical studies conducted using FS as active moiety are also enlisted. Graphical abstract: Image 1 Highlights: Fisetin works through multiple mechanisms for the treatment of various diseases. Poor solubility and poor oral bioavailability of fisetin impediment its therapeutic efficacy. NDDS play major role in overcoming bioavailability challenges associated with fisetin. Research based reviews about therapeutic potential of fisetin and its NDDS are discussed. Patents on pharmaceutical and non-pharmaceutical applications of fisetin are highlighted.